Fundamental research questions in subterranean biology. (25th August 2020) - Mammola, Stefano; Amorim, Isabel R.; Bichuette, Maria E.; Borges, Paulo A. V.; Cheeptham, Naowarat; Cooper, Steven J. B.; Culver, David C.; Deharveng, Louis; Eme, David; Ferreira, Rodrigo Lopes; Fišer, Cene; Fišer, Žiga; et al.
ABSTRACT: Five decades ago, a landmark paper in Science titled The Cave Environment heralded caves as ideal natural experimental laboratories in which to develop and address general questions in geology, ecology, biogeography, and evolutionary biology. Although the 'caves as laboratory' paradigm has since been advocated by subterranean biologists, there are few examples of studies that successfully translated their results into general principles. The contemporary era of big data, modelling tools, and revolutionary advances in genetics and (meta)genomics provides an opportunity to revisit unresolved questions and challenges, as well as examine promising new avenues of research in subterranean biology. Accordingly, we have developed a roadmap to guide future research endeavours in subterranean biology by adapting a well‐established methodology of 'horizon scanning' to identify the highest priority research questions across six subject areas. Based on the expert opinion of 30 scientists from around the globe with complementary expertise and of different academic ages, we assembled an initial list of 258 fundamental questions concentrating on macroecology and microbial ecology, adaptation, evolution, and conservation. Subsequently, through online surveys, 130 subterranean biologists with various backgrounds assisted us in reducing our list to 50 top‐priority questions. These research questions are broad in scope and ready to be addressed in the next decade. We believe this exercise will stimulate research towards a deeper understanding of subterranean biology and foster hypothesis‐driven studies likely to resonate broadly from the traditional boundaries of this field.